Innovative Methods in Teaching the Uzbek Language: Modern Strategies and Advanced Technologies - Dr. Sayed Mohamed Ahmed Korayem (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This research focuses on the international status of the Uzbek language, emphasizing strategies for its development and strengthening its global presence. It also explores innovative methods for teaching Uzbek to foreign students. The study highlights the importance of expanding the use of Uzbek in academic, cultural, and diplomatic spheres, focusing on developing comprehensive learning curricula that integrate modern technology and foster cultural interaction among diverse students. Additionally, it stresses the role of international collaboration between educational and research institutions to ensure sustainable growth and effective dissemination of the language worldwide.